Precision contouring control of five degree of freedom robot manipulators with uncertainty. (26th December 2016) - Nuchkrua, Thanana; Chen, Shyh-Leh
In this article, we apply a result in equivalent errors to a contouring control problem of five degree of freedom robot manipulators. The proposed technique, fuzzy Proportional Integral Derivative (PID) with the robust extended Kalman filter, is employed to stabilize the dynamic of equivalent errors of robot manipulators. The shape of membership functions and rules of fuzzy PID controller are tuned following operating conditions that make the control performance to improve significantly. A desired path in terms of the position of the end-effector of the robot manipulators is described in generalized coordinates defined by the dynamic of equivalent. The simulation and experimental results demonstrate the excellent performance of the proposed technique.